Metamorphic reactions and their implication for the fluid budget in metapelites at seismogenic depths in subduction zones - Rajič, Kristijan; Raimbourg, Hugues; Lerouge, Catherine; Famin, Vincent; Dubacq, Benoît; Canizarés, Aurélien; Di Carlo, Ida; Maubec, Nicolas (Tectonophysics, 2023)
International audience In order to determine fluid-mineral reactions and the fluid budget in subduction zones, we have examined rocks from two accretionary complexes, the Kodiak (Alaska) and Shimanto (Japan), that were buried at the temperature conditions of the seismogenic zone. Maximum burial temperatures based on Raman spectroscopy of carbonaceous material in both examples range from 230 to 350 °C, whereas pressures reached up to ⁓3 and ⁓4kbars (based on multi-equilibrium modelling) in the higher-grade units of the Japanese and Alaskan complexes, respectively. At 230–260 °C, chlorite is interpreted as a coproduct of the lower-grade smectite-to-illite transformation. Chlorite content increases as temperature increases to 330–350 °C, as a result of illite-to-chlorite transformation. Other reactions include pyrite oxidation, dissolution of titanite and precipitation of anatase. Whole-rock chemistry points to the absence of systematic chemical variations in the temperature range between 250 and 350 °C and only local transport of quartz and albite from the matrix, to veins nearby, is observed. Qualitative analyses of the composition of fluid inclusions using decrepitation method show that the composition of the fluid is significantly different from the original seawater trapped in pores. In addition, the salinity of fluid inclusions in the quartz veins at 230–260 °C, analyzed using the Raman spectrum of water, is lower than seawater and interpreted as dilution of the original seawater by the fresh water released by the smectite-to-illite transformation. In contrast, veins formed at 330–350 °C contain fluid inclusions with a salinity on the order of or higher than that of seawater. The increase in salinity for temperatures of 250–350 °C reflects hydration reactions, which are mostly controlled by chlorite crystallization. This study demonstrates an uptake of pore fluid by mineral reactions at temperature corresponding to the base of the seismogenic zone, which is in contrast to the general trend of dehydration ...